The effect of customer retention programs on re-patronage intention: a case of Muar Traders Hotel / Nurulain Atan - Atan, Nurulain (2010)
As market growth slows or as markets become more competitive and level of switching costs increases, firms are more likely to attempt to maintain their market share by focusing on retaining current customers. Customer retention has been advocated as an easier and more reliable source of superior performance. This research utilized a convenience methodology to improve customer retention, and the researcher has helped the firm identifying the factors that contribute to retain customer and initiate a variety of strategies to accomplish this objective. Four customer retention program tools that contribute to re-patronage intention of the customers that had been identify by researcher consists of privilege cards, greeting cards, charity works and free spa. The finding highlights the effectiveness of the retention program tools used by Muar Traders Hotel. The researcher also identified the causes that lead to the decrease of the firm customer retention rate and come out with few recommendations. By implementing the recommendations, the researcher optimism that it will help the firm to better upgrade its performance and any area that is not running well in their management for future use.